Candida meningitis in an infant after abdominal surgery successfully treated with intrathecal and intravenous amphotericin B: A case report. Issue 37 (17th September 2021) - Yuan, Lihua; Chen, Feng; Sun, Yao; Zhang, Yong; Ji, Xing; Jin, Bo
Abstract: Rationale: Studies on Candida infections in the central nervous system, especially in infants and young children that did or did not have postoperative surgery, are rarely reported. Thus far, intrathecal ( i.t. ) amphotericin B (AmB) is not routinely recommended as a therapy for Candida meningitis. We report the first case of Candida meningitis in an infant who underwent abdominal surgery and was successfully treated with i.t. and intravenous (i.v.) AmB in the mainland of China. Patient concerns: Candida meningitis was confirmed by culture and immunoserological tests in a 1-day-old girl after surgery. She was treated with fluconazole for 1 month, but the patient's symptoms showed no improvement. Diagnoses: After surgery, the infant started having recurrent attacks of fever, and laboratory tests of the cerebrospinal fluid (CSF) revealed antigens of Candida tropicalis . CSF tests revealed a high total protein level and a low glucose level. She was diagnosed with a secondary Candida meningitis. Interventions: After azole therapy failure, intrathecal and intravenous AmB therapy were used as rescue therapies. Outcomes: After nearly 2 months of AmB treatment, all repeat CSF cultures were negative, the infant was deemed stable and was discharged home, and she continued taking voriconazole orally as an outpatient. Lessons: The combination of i.t. and i.v. administration of AmB can provide a safe and effective alternative to managing this rare but severe disease.